A review of squeaking in ceramic total hip prostheses. (January 2016) - Askari, Ehsan; Flores, Paulo; Dabirrahmani, Danè; Appleyard, Richard
Abstract: The occurrence of audible squeaking in some patients with ceramic-on-ceramic (CoC) hip prostheses is a cause for concern. Great effort has been dedicated to understand the mechanics of the hip squeaking to gain a deeper insight into factors contributing to sound emission from CoC hip articulation. Disruption of fluid-film lubrication and friction were reported as the main potential cause, while patient and surgical factors, and design and material of hip implants, were also identified as leading factors. This article summarizes the recent available literature on this subject to provide a platform for future research and development. Moreover, high wear rates and ceramic liner fracture as viable consequences of hip squeaking are discussed. Highlights: The recent available literature on ceramic hip squeaking are reviewed. Important factors contributing to hip squeaking are considered. Two main numerical models used to simulate hip squeaking are described. Viable consequences of hip squeaking are discussed. Future research directions in this research area are summarized and discussed.